Long-term weight change and risk of breast cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. (23rd March 2021) - Ellingjord-Dale, Merete; Christakoudi, Sofia; Weiderpass, Elisabete; Panico, Salvatore; Dossus, Laure; Olsen, Anja; Tjønneland, Anne; Kaaks, Rudolf; Schulze, Matthias B; Masala, Giovanna; Gram, Inger T; Skeie, Guri; et al.
Abstract: Background: The role of obesity and weight change in breast-cancer development is complex and incompletely understood. We investigated long-term weight change and breast-cancer risk by body mass index (BMI) at age 20 years, menopausal status, hormone replacement therapy (HRT) and hormone-receptor status. Methods: Using data on weight collected at three different time points from women who participated in the European Prospective Investigation into Cancer and Nutrition (EPIC) study, we investigated the association between weight change from age 20 years until middle adulthood and risk of breast cancer. Results: In total, 150 257 women with a median age of 51 years at cohort entry were followed for an average of 14 years (standard deviation = 3.9) during which 6532 breast-cancer cases occurred. Compared with women with stable weight (±2.5 kg), long-term weight gain >10 kg was positively associated with postmenopausal breast-cancer risk in women who were lean at age 20 [hazard ratio (HR) = 1.42; 95% confidence interval 1.22–1.65] in ever HRT users (HR = 1.23; 1.04–1.44), in never HRT users (HR = 1.40; 1.16–1.68) and in oestrogen-and-progesterone-receptor-positive (ER+PR+) breast cancer (HR = 1.46; 1.15–1.85). Conclusion: Long-term weight gain was positively associated with postmenopausal breast cancer in women who were lean at age 20, both in HRT ever users and non-users, and hormone-receptor-positive breast cancer.